Social and Emotional Learning as Through the Views of Teachers Applying STEM Approach in Learning - Veneta Uzunova (Педагогически форум)
The development and application of the STEM approach in education is in the focus of contemporary research work. STEM based learning creates premises for problem solving on your own and in a team, managing conflict situations, finding your own place in the team, the skills to express and argue a position, skills for active listening and going deeper into other’s point of view, “outside of the box” thinking. Social and emotional learning in itself is an approach for the creation and the development of competencies in areas such as: self-awareness, decision making, self-respect, social awareness and social skills. The current article presents the results of a conducted research among teachers implementing the STEM approach in their teaching. It is an attempt to establish through reflection and self-reflection an answer to the question to what extent do they think of social and emotional learning as they implement STEM and what social and emotional skills are being developed in both students and teachers through STEM.